Digital Exposure and Regret: The Mediating Role of FoMO In Post-Event Consumer Behavior - Wijaya, Anita Carolina; Yuniawati, Yeni; Ridwanudin, Oce (Journal of Entrepreneurship & Business, 2026)
Purpose: This study investigates the impact of digital exposure on post-purchase regret among K-pop concert attendees, specifically examining the mediating role of Fear of Missing Out (FoMO). By utilizing the Stimulus-Organism-Response (S-O-R) framework, the research aims to explain how the hyper-connected digital ecosystem of K-pop fandom translates intensive information flow into long-term emotional dissatisfaction. Method: A quantitative research design was employed, collecting data from 185 K-pop fans in Indonesia through a web-based questionnaire. The sample was dominated by Generation Z females (79.5%), reflecting the core demographic of the fandom. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 to test the direct and indirect relationships between digital exposure, FoMO, and post-purchase regret. Result: The findings confirm that all hypotheses were accepted. Digital exposure has a significant positive effect on both post-purchase regret (β = 0,299, p < 0,004, t > 2,843), and FoMO (β = 0,643, p < 0,000, t > 13,634). FoMO also significantly influences post-purchase regret (β = 0,385, p < 0,000, t > 4,293). Most importantly, FoMO was found to partially mediate the relationship between digital exposure and post-purchase regret (β = 0,248, p < 0,000, t > 3,770). The model explains 41.4% of the variance in FoMO and 38.6% in post-purchase regret.